391 Young Scholar Award Talk: Supplementation of Oligosaccharide-Based Polymer Enhanced Growth and Disease Resistance of Weaned Pigs by Modulating Intestinal Integrity and Systemic Immunity. (21st September 2022) - Kim, Kwangwook; He, Yijie; Jinno, Cynthia N; Kovanda, Lauren L; Li, Xunde; Bravo, David; Cox, Eric; Liu, Yanhong
Abstract: Oligosaccharides have been reported to possess ETEC receptor activity for bacterial adhesions; thus, additional supplementation may efficiently prevent enterotoxin-induced secretory diarrhea. Moreover, grafted polymers that combine multiple substances have been proposed for their potential synergistic effects on preventing human and animal diseases. Therefore, the objective of this experiment was to investigate dietary supplementation of oligosaccharide-based polymer on growth performance, diarrhea severity, intestinal health, and systemic immunity of weaned pigs experimentally infected with an enterotoxigenic Escherichia coli (ETEC) when compared with in-feed antibiotics. Forty-eight pigs (7.23 ± 1.11 kg BW) were individually housed in disease containment rooms and randomly allotted to one of four treatments with 12 replicate pigs per treatment. The four dietary treatments were a nursery basal diet (CON), and 3 additional diets supplemented with 50 mg/kg antibiotics (Carbadox; CAR), 10 or 20 mg/kg of oligosaccharide-based polymer (OBP). The experiment lasted 18 d [7 d before and 11 d after the first inoculation (d 0)]. All pigs were orally inoculated with 3mL of F18 ETEC for 3 consecutive days from d 0 post-inoculation (PI). Growth performance and diarrhea severity were measured throughout the experiment. Blood, lymph nodes, spleen, and intestinal mucosa samples were collected during the peak infection period (d 2 and d 5 PI) and recovery period (d 11 PI). Pigs in CAR or OBP treatment groups had greater (P<0.05) body weight on d 5 or d 11 PI than pigs in the CON group, respectively. Supplementation of CAR or OBP enhanced (P<0.05) feed efficiency from d 0 to 5 PI and reduced (P<0.05) frequency of diarrhea throughout the experiment, compared with pigs in the CON group. Pigs in CAR or OBP groups had reduced (P<0.05) neutrophil counts and serum haptoglobin concentration compared to pigs in the CON group on d 2 and 5 PI. Pigs in OBP reduced (P<0.05) total coliforms in mesenteric lymph nodes on d 5 and 11 PI, whereas pigs in CAR or OBP groups had reduced (P<0.05) total coliforms in the spleen on d 11 PI compared with pigs in the CON group. On d 5 PI, pigs in the OBP group had greater (P<0.05) gene expression of ZO1 in jejunal mucosa, but less (P<0.05) mRNA expression of IL1B, IL6, and TNF in ileal mucosa, in comparison with pigs in the CON group. On d 11 PI, supplementation of CAR or OBP up-regulated (P<0.05) gene expression of CLDN1 in jejunal mucosa, but OBP reduced (P<0.05) IL6 gene expression in ileal mucosa compared to pigs in the CON group. In conclusion, supplementation of oligosaccharide-based polymer improved growth performance, alleviated diarrhea severity, and enhanced gut health in weaned pigs infected with ETEC F18 in a manner similar to in-feed antibiotics.